2005
DOI: 10.1016/j.bbrc.2005.08.105
|View full text |Cite
|
Sign up to set email alerts
|

Selection of and recombination between minor variants lead to the adaptation of an avian coronavirus to primate cells

Abstract: An interesting question posed by the current evidence that severe acute respiratory syndrome coronavirus may be originated from an animal coronavirus is how such an animal coronavirus breaks the host species barrier and becomes zoonotic. In this report, we study the chronological order of genotypic changes in the spike protein of avian coronavirus infectious bronchitis virus (IBV) during its adaptation to a primate cell line. Adaptation of the Beaudette strain of IBV from chicken embryo to Vero cells showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
77
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 21 publications
(22 reference statements)
0
77
0
Order By: Relevance
“…But only a few studies have examined changes across the entire genome associated with biological characteristics of the virus [22,31]. Ammayappan et al [22] found a total of 17 amino acid changes between the genomes of Ark DPI 11, a pathogenic virus and Ark DPI 101 an attenuated virus, with four amino changes in nsp 3 and six amino acid changes in the S1 glycoprotein.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…But only a few studies have examined changes across the entire genome associated with biological characteristics of the virus [22,31]. Ammayappan et al [22] found a total of 17 amino acid changes between the genomes of Ark DPI 11, a pathogenic virus and Ark DPI 101 an attenuated virus, with four amino changes in nsp 3 and six amino acid changes in the S1 glycoprotein.…”
Section: Discussionmentioning
confidence: 98%
“…Based on that data, it was suggested that changes in the replicase sequence in addition to structural proteins might play a role in pathogenicity. Fang et al [31] found 53.06% of all amino acid substitutions across the entire genome were located in the spike glycoprotein following adaptation of an attenuated avian coronavirus to primate cells, suggesting that spike plays a role in host adaptation.…”
Section: Discussionmentioning
confidence: 98%
“…Once the dominant strain is stable and adapted to a new host cell, adaptation is a rapid process (FANG et al, 2005) and thus the fixation of the Master Sequences in CCoV might have been a result of this stability mainly due to neutral evolution, as shown herein by the selection regime analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of IBV to vary its genome and form new strains via natural or induced recombination has been suggested and examined in several investigations (Kusters et al, 1990;L. Wang et al, 1993;Jia et al, 1995;Kottier et al, 1995;Lee & Jackwood, 2000Wang & Huang, 2000;Estevez et al, 2003;Brooks et al, 2004;Stavrinides & Guttman, 2004;Fang et al, 2005;Dolz et al, 2006Dolz et al, , 2008Pyrc et al, 2006;Chen et al, 2009). This emphasizes the immense diversity of coronaviruses and their potential to produce numerous new strains, with differing pathogenicity and heterologous serotypes compared with the parent strains, through recombination alone.…”
Section: Discussionmentioning
confidence: 99%